Who’s at Fault? Tata Sons in 2012 or Mistry in 2016: A Case Study on Tata Group - Jain, Divya (IIUM Journal of Case Studies in Management, 2018)
Tata group is an Indian MNC founded in 1868 by Jamsetji Tata. His vision envisaged towards nation’s development to see India self-sufficient. The company was headed by JRD Tata during 1939-90. His tenure made a significant contribution towards the growth of the group. In 1991, Ratan Tata took over as a chairman of Tata group of companies. His clear vision and desire to achieve along with people’s support made the company grow 57 times from the year he was appointed. Since Tata lacked an heir, Cyrus Mistry, second largest shareholder in Tata sons who worked very closely with Ratan and ensured the best of his capabilities with a long term association and commitment, was appointed as the new chairman of Tata Group in 2012, after being on a position of Deputy Chairman for about a year. His leadership viewed major strategic decisions that affected Tata’s market image and growth, in the view of Tata trusts. In 2016, a sudden decision of Mistry’s exit raised several questions on the governance at the Tata group and the succession experiment that went wrong. The case also talks about the deviations in leadership style and reasons for the elevating trust deficit among the people concerned.